The Reduction and Simplification of English Grammar during Computer Mediated Communication in Pakistani Context - Amnah Moghees; Saima Abbas Dar; Mehr unisa Zaid; Muniba Saeed (Linguistics and Literature Review, 2017)
Computer Mediated Communication (CMC) is proliferating like anything in our lives. Communication theorists have been exploring its various dimensions; however, CMC grammar appears to be a less attempted area. The concept of CMC grammar seems to be an emerging phenomenon in mediated- communication. To explore this phenomenon, the present study sets out to investigate the identified forms of CMC grammar of students at graduate level in Pakistan. A sample of 50 BS students was chosen to address the core research questions. The data was collected primarily from the verbal postings of the participants from facebook walls of selected students. To avoid superficiality, the study was backed by imperial findings and factual details. The study reveals that English Grammar is subject to reduction and simplification in computer mediated-communication. The elements of reduction and simplification can be characterised by subject omission, copula deletion and absence of auxiliaries in progressive and interrogative situation. These features are so widespread that they are increasingly getting stable and intelligible across the board. The study speculates that ever- increasing proliferation of these features signposts a unique grammar which is the central investigation of this study.